Prediksi Potensi Kebangkrutan Menggunakan Metode Analisis Altman Z-Score, Springate Score dan Zmijewski Score pada PT XYZ - Bella Jelina Putri; Eksa Ridwansyah; Arif Makhsun (Politeknik Negeri Lampung, 2020)
This final task report aims to find out the potential for bankruptcy in PT XYZ by using the Altman Z-Score, Springate Score, and Zmijewski Score analysis methods. The analysis method used in compiling this final task report is a quantitative method because the research is done by way of analysis based on numbers and data that have been obtained. Based on the results of the discussion can be concluded from the results of the analysis of predictions of potential bankruptcy using the altman Z-Score, Springate Score, and Zmijewski Score analysis methods that PT XYZ during the period 2016 - 2018 is in the danger zone or included in the criteria of companies that are potentially bankrupt. However, PT XYZ can still carry out its company's operations and PT XYZ strives to improve its financial condition.